Effect of cation type, alkyl chain length, adsorbate size on adsorption kinetics and isotherms of bromide ionic liquids from aqueous solutions onto microporous fabric and granulated activated carbons - Hassan, S. (Academic Press, 2014)
The adsorption from aqueous solution of imidazolium, pyrrolidinium and pyridinium based bromide ionic liquids (ILs) having different alkyl chain lengths was investigated on two types of microporous activated carbons: a fabric and a granulated one, well characterized in terms of surface chemistry by "Boehm" titrations and pH of point of zero charge measurements and of porosity by N2 adsorption at 77K and CO2 adsorption at 273K. The influence of cation type, alkyl chain length and adsorbate size on the adsorption properties was analyzed by studying kinetics and isotherms of eight different ILs using conductivity measurements. Equilibrium studies were carried out at different temperatures in the range 25-55Â°C. The incorporation of ILs on the AC porosity was studied by N2 adsorption-desorption measurements at 77K. The experimental adsorption isotherms data showed a good correlation with the Langmuir model. Thermodynamic studies indicated that the adsorption of ILs onto activated carbons was an exothermic process, and that the removal efficiency increased with increase in alkyl chain length, due to the increase in hydrophobicity of long chain ILs cations determined with the evolution of the calculated octanol-water constant (Kow). The negative values of free energies indicated that adsorption of ILs with long chain lengths having hydrophobic cations was more spontaneous at the investigated temperatures. Â© 2014 Elsevier Ltd.